Reduced phosphorylation of ribosomal protein S6 is associated with sensitivity to MEK inhibition in gastric cancer cells. Issue 12 (19th December 2016) - Hirashita, Yuka; Tsukamoto, Yoshiyuki; Yanagihara, Kazuyoshi; Fumoto, Shoichi; Hijiya, Naoki; Nakada, Chisato; Uchida, Tomohisa; Matsuura, Keiko; Kodama, Masaaki; Okimoto, Tadayoshi; Daa, Tsutomu; Seike, Masataka; et al.
Abstract : Gastric cancer (GC) is characterized by amplifications of receptor tyrosine kinases (RTK) and KRAS, therefore, targeting of the RTK/KRAS downstream pathways could help to broaden the applicability of molecular targeted therapy for GC. We assembled a panel of 48 GC cell lines and screened predictors of responsiveness to inhibition of the RAF/MEK/ERK pathway, one of the RTK/KRAS downstream pathways. We found that GC cells with MET amplification or KRAS mutation, but not amplification, tended to be sensitive to MEK inhibition. However, several cell lines without RTK/KRAS alterations also showed high sensitivity to MEK inhibition. We then focused on the phosphorylation of RTK/KRAS downstream molecules to screen for predictors' sensitivity to MEK inhibition. We found that the phosphorylation level of mammalian target of rapamycin complex 1 (mTORC1) downstream molecules, including p70S6K, 4EBP1, and S6, was significantly associated with sensitivity to MEK inhibition in GC cells ( P < 0.05), suggesting that mTORC1 activity is related to the sensitivity to MEK inhibition. Furthermore, the change in mTORC1 activity after MEK inhibition was also significantly associated with this sensitivity ( P < 0.001). Among the mTORC1 downstream molecules, the change in S6 phosphorylation (pS6) showed the most significant correlation with sensitivity. Using xenograft models derived from highly sensitive and resistant cell lines, we found specific reduction of pS6 in xenografts from highly sensitive cell lines after 6 h of treatment with an MEK inhibitor. Thus, our data suggest the potential clinical applicability of an MEK inhibitor for a proportion of GC patients who could be selected on the basis of pS6 change after MEK inhibition. Abstract : Gastric cancer is genetically so heterogeneous that particular genomic alterations is not valid for the prediction of sensitivity to molecular targeting drugs. In this study, we propose a new concept that would allow patients to be selected on the basis of the phosphorylation level of signaling molecules and targeting of a common pathway downstream from various types of genomic alterations.